EFEKTIVITAS KEGIATAN KELOMPOK USAHA BERSAMA (KUBE) RAFFLESIA KABUPATEN BENGKULU UTARA - Devia Wanda; Ilham Adbullah; Parlan Parlan (Jurnal Pendidikan Sepanjang Hayat, 2019)
General objective of this study was to determine the effectiveness of activities done by Rafflesia Business Group at the North Bengkulu. And the specific purpose of this study was to determine the planning, implementation, efforts to increase its capabilities to the members in the group, infrastructure, and the evaluation of Business Group program. The method of this study was a qualitative method and the data collection techniques used was interview, observation and documentation. The subjects of this research was Rafflesia Business Group board consisted of Chairman, Secretary, Treasurer and Members. In order to prove the validity of the research, it was checked by using the triangulation of data sources, techniques and timing. Data were analyzed through three stages, which were data reduction, presentation and conclusion. The research found that the first, Rafflesia Business Group did not use specific standards in planning the program it was only seen from the public interest, the planning was done with the consensus of the members. Second, implementation, Rafflesia Business Group implemented the program in accordance with the initial plan that had been prepared in advance with the cooperation of members to achieve production. Third, the efforts to increase the member participation in the group, members of the business made another attempt at Business Group. But they were always working to improve Business Group program in order to create new innovations. Fourth, influence of infrastructure, KUBE Rafflesia had sufficient infrastructure and assist in achieving the results of Business Group’s program. Fifth evaluation, the evaluation was done associated with the planning done by the consensus of members, the implementation that was done matched with the advance planning in which the members were cooperated, the efforts to increased members participation in which they were always attempted to give new innovations for Business Group’s program, and the infrastructure supported in achieving the results of Business Group. Keywords: Effectiveness, Business Group, entrepreneurship